2023
DOI: 10.1101/2023.02.07.23285508
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development of minimum reporting sets of patient characteristics in epidemiological research: a methodological systematic review

Abstract: Background: Core patient characteristic sets (CPCS) are increasingly developed to identify variables that should be reported to describe the target population of epidemiological studies in the same medical area, while keeping the additional burden on the data collection acceptable. Methods: We conduct a systematic review of primary studies/ protocols published aiming to develop CPCS, using the PubMed database. We particularly focus on the study design and the characteristics of the proposed CPCS. Quality of De… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…18,20,21 While CPCS should be further considered in the future, rationales for covariate selection should always be included when conducting a PAIC analysis. 3,22 Third, we observed that a large number of studies did not assess the potential overlap of covariate distribution between populations before and after adjustment. In a PAIC analysis, although the target populations of different studies might be different, it is important that they are still sufficiently similar so that we can learn about one population via observing the other without erroneous extrapolations.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…18,20,21 While CPCS should be further considered in the future, rationales for covariate selection should always be included when conducting a PAIC analysis. 3,22 Third, we observed that a large number of studies did not assess the potential overlap of covariate distribution between populations before and after adjustment. In a PAIC analysis, although the target populations of different studies might be different, it is important that they are still sufficiently similar so that we can learn about one population via observing the other without erroneous extrapolations.…”
Section: Discussionmentioning
confidence: 97%
“…Across many therapeutic areas, a so‐called core patient characteristic set (CPCS) is specifically developed to identify all key prognostic factors that should be commonly collected and reported (among studies and databases evaluating a similar target condition), while keeping the additional burden on the implementation acceptable 18,20,21 . While CPCS should be further considered in the future, rationales for covariate selection should always be included when conducting a PAIC analysis 3,22 …”
Section: Discussionmentioning
confidence: 99%